34 A HYPEROSMOLAR DENSITY GRADIENT EFFICIENTLY SEPARATES CD4+ CELLS FROM RESPIRATORY MUCINS. (1st March 2005) - Sachdeva, R.; Meyers, S. B.; Freishtat, R. J.
Abstract : Objective: Recent studies have shown that CD4+ T lymphocytes are recruited into the lung to mediate inflammation in asthma. Previous work has shown that examining these cells in peripheral blood is useful in the study of asthma; however peripheral cells likely do not represent the same phenotype as those found in the lungs. Previous attempts to isolate mononuclear cells (MNC) from lung washings have been frustrated by mucin contamination. The ability to isolate these cells from the lungs would provide a means to better understand their role in the local pulmonary inflammation of asthma. To develop a density gradient technique for isolating CD4+ cells from lung washings. Methods: Lung washings were collected in a standardized fashion from intubated patients with mucoid secretions into Lukens traps with Na-heparin and EDTA added. Samples were flowed through a 60-mesh steel screen to remove large clumps of mucus and then layered on a series of discontuous hyperosmolar density gradients, ranging from 350 to 425 mOsm, and 1.060 to 1.095 g/mL. The gradients were centrifuged and the MNC layer was removed from the mucin layer and resuspended. The CD4+ cells were then negatively isolated using a magnetic colloid-bound antibody technique. Flow cytometry was performed to determine the purity of resulting isolates. Results: Mucin contamination remained significant throughout the range of densities and concentrations. At lower densities and concentrations, the mucin contamination was more significant. However, at a concentration of 425 mOsm and density gradient of 1.085-1.090-1.095 g/mL, MNC were found to pellet under the 1.095 g/mL density layer, while the mucins remained suspended within the 1.085-1.090 regions. After resuspension, cell viability was found to be>95% by Trypan blue exclusion. Flow cytometry of the CD4+ enriched-isolates from these samples demonstrated a CD3+CD4+ purity>95%. Conclusions: This hyperosmolar density gradient technique is useful for obtaining pure viable CD4+ cell isolates from mucus in lung washings. This represents an additional tool for the study of the role of these and other MNC in local lung inflammation in acute asthma.